2014
DOI: 10.1111/jicd.12106
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Malay version of the Modified Dental Anxiety Scale and the prevalence of dental anxiety in a Malaysian population

Abstract: The Malay version of the MDAS had good reliability and validity. Anxiety levels found in the Malaysians studied were comparable to participants from other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 30 publications
8
16
1
Order By: Relevance
“…erefore, groups that were known to differ in their levels of dental anxiety (e.g., age, sex, dental attendance patterns, and negative experiences) were compared with the scores that were yielded by the Japanese version of the MDAS in the present study. e present results suggest that mean MDAS scores decrease as age increases in agreement with many studies in UK, Italian, Arabic, Indian (Kannada and Tamil), Chinese, and Malay populations [15][16][17][18][19][20][21], whereas a study in Turkey reported that MDAS scores increased with age [34]. In the present study, female patients reported higher levels of dental anxiety than male patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…erefore, groups that were known to differ in their levels of dental anxiety (e.g., age, sex, dental attendance patterns, and negative experiences) were compared with the scores that were yielded by the Japanese version of the MDAS in the present study. e present results suggest that mean MDAS scores decrease as age increases in agreement with many studies in UK, Italian, Arabic, Indian (Kannada and Tamil), Chinese, and Malay populations [15][16][17][18][19][20][21], whereas a study in Turkey reported that MDAS scores increased with age [34]. In the present study, female patients reported higher levels of dental anxiety than male patients.…”
Section: Discussionsupporting
confidence: 91%
“…e Japanese version of the MDAS demonstrated a high Cronbach's alpha value. Cronbach's alpha value of the Japanese version was relatively similar to the Finnish and Arabic version [32], the Italian version showed higher [16], and the Nepali [33] and Malay [21] versions showed lower values than the Japanese version among dental patients (shown in Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire used in this study comprised of the mother's and child's socio-demographic information, the Malay version of the Modified Dental Anxiety Scale (Malay-MDAS) [32], the Malay version of the Modified Child Dental Anxiety Scale faces version (Malay-MCDAS f ) [33] , and the Malay version of the Early Childhood Oral Health Impact Scale (Malay-ECOHIS) [31]. Family monthly incomes were categorised into low (MYR < 1500), moderate (MYR 1500 to 3500), and high income (> MYR 3500) in line with the minimum wage in Malaysia during the data collection period [34].…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, the process of completion does not raise the patient's anxiety level [ 9 ]. MDAS has been translated into different languages, namely, Arabic, Chinese, Greek, Romanian, Spanish, Tamil, Turkish, and Italian [ 10 ]. It has a good cross-cultural reliability and validity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%